PENANAMAN KARAKTER DERMAWAN MELALUI SEDEKAH - Nofiaturrahmah, Fifi (UIN Sunan Kudus, 2017)
Generosity is a character, a character rarely found in a person. In Islam teaches its people to have the character or the character of generosity with the aim to have a sense of gratitude towards the favors of Allah, manifesting high social sensitivity, and the realization of a community that likes to help. Generosity is a character or character that is rarely found in a person not everyone has a generous character, especially in adolescents today. Teenagers are currently more likely and busy with his world and his youth. Teenagers are currently less sensitive to the environment around them, especially in the environment that needs one>s help. One institution in instilling one character is the character of generosity through the activities of infak and alms. Through the methods, strategies, approaches and forms of planting through various activities both in daily habituation activities.